La variabilité pluviométrique et ses impacts sur les rendements et les surfaces cultivées dans le bassin arachidier de la région de Thiès (Sénégal) - Souleymane Diallo; MBagnick Faye; Hassan Bismarck Nacro (VertigO, 2022)
This study aims to analyze the impacts of rainfall variability on agricultural yields in the groundnut basin of the Thies region. Rainfall variability and declining rainfall volumes are characteristics of the groundnut basin in the Thies region, as they are in other Sahelian countries. There has been a significant water deficit in the study area since the 1970s. This deterioration in rainfall conditions has impacted the socio-economic activities of the population, particularly agriculture. A statistical analysis (Pettitt break test, drought index, ten-year rainfall trend) of rainfall and agricultural data from 1961-2016 revealed an irregular spatio-temporal distribution of rainfall volumes. This study also shows a weak correlation between rainfall and agricultural yields. Therefore, annual rainfall volumes alone do not determine yields. Yields of millet, cowpea, and cassava varied only slightly during the 1970s despite the drought, in contrast to groundnuts, which declined in all three departments of the Thies region because of the drought. Other factors include dry spells, seed quality, soil fertility, crop predators, etc. The different sensitivity of crops to drought in Thies contributes to choosing the best options for successful adaptation.